Grain boundary structure and intergranular stress corrosion crack initiation in high temperature water of a thermally sensitised austenitic stainless steel, observed in situ - Stratulat, A; Duff, J; Marrow, T (Elsevier, 2014)
The development of an intergranular stress corrosion crack initiation site in thermally sensitised type 304 austenitic stainless steel has been observed in situ in high temperature oxygenated water using digital image correlation of time-resolved optical observations. The grain boundary normal stresses were calculated using the Schmid-Modified Grain Boundary Stress (SMGBS) model of Was et al., applying three-dimensional data for the grain boundary planes and grain orientations. The initiation site coincided with the most highly stressed sensitised boundary, demonstrating the importance of the combined contributions to crack initiation of grain boundary structure and plastic strain incompatibility.